Relationship of psychological flexibility and mindfulness to caregiver burden, and depressive and anxiety symptoms in caregivers of people with dementia - Khai, Pin Tan; Jin, Kiat Ang; Eugene, Boon Yau Koh; Nicholas, Tze Ping Pang; Mat Saher, Zanariah (Multidisciplinary Digital Publishing Institute, 2023)
Caregivers of People with dementia (PwD) commonly experience burdens and other mental health issues, e.g., depression and anxiety. At present, there are limited studies that examine the relationships between caregiver psychological factors and caregiver burden, and depressive and anxiety symptoms. Therefore, this study’s objectives were to examine the relationships between psychological flexibility and mindfulness in caregivers of PwD, and to determine the predictors of these three outcomes. This was a cross-sectional study conducted in the geriatric psychiatry clinic of Kuala Lumpur Hospital, Malaysia, and the sample (n = 82) was recruited via a universal sampling method over three months. The participants completed a questionnaire that consisted of the sociodemographics of the PwD and caregivers, illness characteristics of the PwD, Acceptance and Action Questionnaire-II (AAQ-II), Mindful Attention Awareness Scale (MAAS), Zarit Burden Interview Scale (ZBI), Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7). The results show that despite significant relationships between psychological flexibility and mindfulness and lower levels of caregiver burden, and depressive and anxiety symptoms (p < 0.01), only psychological inflexibility (p < 0.01) remained as a significant predictor of the three outcomes. Therefore, in conclusion, intervention programs that target the awareness of the caregiver’s psychological inflexibility should be implemented to alleviate these adverse outcomes in dementia caregivers.